40. THE PRESENT STATE OF HEALTH CARE REQUIREMENTS BASED ON THE FAMILY MEDICINE MODEL FOR RESIDENTS OF THAI NGUYEN CITY IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to assess the current status and identify key factors influencing the demand for healthcare services within the family medicine model in Thai Nguyen city in 2024.Method: 425 residents of Thai Nguyen city participated in a cross-sectional descriptive study.Results: According to the family medicine model, 41.6% of persons have health care needs. Good service quality (37.9%) and good service costs (45.2%) are the most prevalent reasons for seeking it. The most commonly cited reason for non-participation in the model is its relative novelty and limited public awareness (40.3%). The family medicine model identifies several elements influencing health care demand: income and education levels, the pursuit of high-quality services, favorable perceptions of medical staff, affordability, and apprehension towards novel and unconventional models.Conclusion: Family medicine is an essential part of the health system, and in order to better meet the medical requirements of the community, efforts must be made to raise public knowledge of it and support its expansion and replication.
Keywords: Family medicine; general practitioner